Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/nyas.14508
|View full text |Cite
|
Sign up to set email alerts
|

Optimal preoperative neoadjuvant therapy for resectable locally advanced esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the most common malignancies worldwide, especially in East Asia. ESCC accounts for more than 90% of esophageal cancer. Currently, neoadjuvant therapy in combination with surgical resection is the mainstay of treatment. However, the overall survival rate of patients with locally advanced ESCC is not satisfactory even when treated following the standard treatment guidelines. With neoadjuvant chemoradiotherapy, chemotherapy, or emerging immunotherapy, continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 58 publications
1
42
0
Order By: Relevance
“…Trials showed that neoadjuvant chemoradiotherapy improved the OS compared with all other treatment modalities, including neoadjuvant chemotherapy, neoadjuvant radiotherapy and surgery alone. However, the risk of postoperative mortality after neoadjuvant chemoradiotherapy also increased significantly compared with that of surgery alone or neoadjuvant chemotherapy + surgery (9). So patients who received neoadjuvant chemoradiotherapy are relatively less and are more likely to receive neoadjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Trials showed that neoadjuvant chemoradiotherapy improved the OS compared with all other treatment modalities, including neoadjuvant chemotherapy, neoadjuvant radiotherapy and surgery alone. However, the risk of postoperative mortality after neoadjuvant chemoradiotherapy also increased significantly compared with that of surgery alone or neoadjuvant chemotherapy + surgery (9). So patients who received neoadjuvant chemoradiotherapy are relatively less and are more likely to receive neoadjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…2 The mortality and incidence rates of ESCC are currently higher in East Asian countries, especially in China. 3 Previously, surgery alone was the standard primary treatment modality for early ESCC, offering a 5-year survival rate of up to 80%. However, surgery alone yields poor outcomes, and the mortality rate is up to 5% for locally advanced ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…East Asia had the highest incidence of EC, and China had the heaviest burden [1]. The current clinical treatment of EC included surgery, targeted drug therapy, adjuvant radiotherapy and chemotherapy [22][23][24][25][26][27]. However, only relying on current medical technology, the ve-year survival rate was only between 15%-20% [3] .…”
Section: Discussionmentioning
confidence: 99%